2007
DOI: 10.1073/pnas.0709388104
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility in the ABC transporter MsbA: Alternating access with a twist

Abstract: lipid flippase ͉ membrane protein structure ͉ multidrug transport

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

69
1,007
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 724 publications
(1,099 citation statements)
references
References 68 publications
69
1,007
12
Order By: Relevance
“…From the viewpoint of structures, ABC transporters that utilize the alternating access mechanism are believed to undergo large conformational changes upon ATP binding and hydrolysis (Dawson & Locher, 2006; Ward et al , 2007), whereas McjD so far appeared to be more “rigid” (Bountra et al , 2017). So far, our only evidence that McjD adopts an outward‐open conformation was from transport data using a cross‐linked TMD between TMs1‐2 and TMs1′‐2′ (Bountra et al , 2017).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 4 more Smart Citations
“…From the viewpoint of structures, ABC transporters that utilize the alternating access mechanism are believed to undergo large conformational changes upon ATP binding and hydrolysis (Dawson & Locher, 2006; Ward et al , 2007), whereas McjD so far appeared to be more “rigid” (Bountra et al , 2017). So far, our only evidence that McjD adopts an outward‐open conformation was from transport data using a cross‐linked TMD between TMs1‐2 and TMs1′‐2′ (Bountra et al , 2017).…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…Here, we probed the opening of the McjD TMD by smFRET by placing FRET labels at TM1 and 1′. MsbA adopts the expected outward‐open conformation in the presence of nucleotides by movement of TMs1‐2 toward the opposite protomer that causes subunit intertwining (Ward et al , 2007). Our detergent data revealed that the TMD of McjD does not adopt an outward‐open conformation in the presence of nucleotides alone consistent with our previous PELDOR experiments (Fig 2C; Bountra et al , 2017).…”
Section: Discussion and Outlookmentioning
confidence: 99%
See 3 more Smart Citations